(untitled) - Alli, Inteaz (Boca Raton, Fl., 2003)
The book presents the most up-to-date, recognized principles, practices and terminology in the field of food quality management. It provides a clear, concise introduction to the principles of food quality and methods for ensuring food safety, including thorough coverage of both HACCP and the ISO 9000:2000 standards.
Keywords: Food industry and trade; Quality control